Meningkatkan Pemanfaatan Sistem Antrian Online JKN Mobile melalui Intervensi Pendidikan Berbasis Komunitas (Program SEHATI) di Puskesmas Sungai Kapih - Putri, Salwa Az Zahra; Fahmi, Achmad Sabrani; Sa'diyah, Putri Wahiddatus; Asysyifa, Thisna Nugra; Juniarti, Tirsa Aulia; Saefurrohim, Muhamad Zakki (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Problems in health service delivery at Sungai Kapih Primary Health Center include the low utilization of the Mobile JKN online queue system and limited public understanding of service flow procedures. This community service activity aimed to improve public understanding and support the utilization of the Mobile JKN online queue system through the SEHATI (Sehat dan Tertib Antrean) Program as a community-based educational intervention. The activity was conducted in the form of Field Learning Practice (PBL) by students under the supervision of lecturers and staff of Sungai Kapih Primary Health Center from December 18, 2025 to January 22, 2026. Methods included direct observation, interviews with health workers, and focus group discussions to identify service problems and formulate appropriate intervention strategies. Program implementation consisted of educational sessions, direct assistance in using the Mobile JKN application, and dissemination of information regarding service flow and online queue procedures through visual educational media. Quantitative before–after data regarding the increase in understanding and online queue utilization were not comprehensively available during the implementation period. Therefore, the results primarily describe the implementation process and educational intervention carried out through the SEHATI Program. Observational findings and brief interviews indicated improved patient awareness and understanding regarding the use of the Mobile JKN online queue system. The main output of this activity was the provision of a SEHATI standing banner as a sustainable informational medium placed in the service area of the primary health center.